Oral comvound nevus: Rarest of rare - Karthikeya Patil; L Ambika; K P Mahesh (Wolters Kluwer Medknow Publications, 2009)
Nevi are benign proliferations of nevus cells located either entirely within the epithelium, in both the epithelium and underlying stroma, or in the subepithelial stroma alone. Nevi of the oral cavity are usually called mucosal melanocytic nevi or intramucosal nevi. A nevus occurring in the oral cavity is less compared to other areas of the body. There are only few case reports which have depicted about the occurrence of a compound nevus in the oral cavity. These available case reports also quote palate and buccal mucosa as the common sites for the occurrence of a compound nevus. The present case is about a compound nevus on the mandibular anterior attached gingiva. The histopathological analysis confirmed the diagnosis as compound nevus.